PENGGUNAAN TEKNOLOGI AUGMENTED REALITY UNTUK PENUNJANG SISTEM PEMINJAMAN BUKU - Rini Puji Astutik; Hendra Ari Winarno; Novaltino Syarif Hidayahtullah (Universitas Islam Lamongan, 2023)
Along with the changing of book into the digital book, so that the conventional library will be gradually left. To overcome this situation thus the improvement service is needed especially book lending access, then academic people can lend the book easier or more flexible. The Augmented Reality (AR) Technology is the newest technology which has been used a lot in many daily activities. One of them is access system into book in library without enter in. By designing application based on AR for accessing book lending in library where it can do it at some places that is set previously. Each place where has been set is given marker to confirm to where the book is delivered. Beside lending book, there are some other features to make easy on choosing the book and application guidance. The result simulation shown that this application run as the design and can access the book which has been input into application. This application has been stored in Play Store as android application so that it will be easier for everyone accessing.